2022
DOI: 10.24018/ejedu.2022.3.6.487
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Self-Confidence Reinforcement on Changes in Students’ Cognitive Ability in Collaborative Learning

Abstract: Self-confidence as an important psychological component in the academic learning process is always interesting to review in various situations and learning models for physical education students, both in schools and colleges environment. Reinforcement that strengthens the quality of students’ self-confidence is something that might have a significant impact on improving students’ cognitive and even overall learning outcomes. This study aims to investigate the effect of reinforcement performed by the teacher on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…They observed that professional qualifications primarily influenced certain socioemotional skills crucial for effective teaching, suggesting that teacher performance is a complex construct influenced by a variety of factors beyond academic qualifications. Moreover, the recent research by Yudho et al (2022), emphasizing the roles of emotional intelligence and self-confidence in teacher performance, adds another layer to our understanding (10). This aligns with the findings from Karachi, where other factors beyond gender and educational qualifications might be more influential in determining teacher performance.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…They observed that professional qualifications primarily influenced certain socioemotional skills crucial for effective teaching, suggesting that teacher performance is a complex construct influenced by a variety of factors beyond academic qualifications. Moreover, the recent research by Yudho et al (2022), emphasizing the roles of emotional intelligence and self-confidence in teacher performance, adds another layer to our understanding (10). This aligns with the findings from Karachi, where other factors beyond gender and educational qualifications might be more influential in determining teacher performance.…”
Section: Discussionsupporting
confidence: 73%
“…These tools have been previously used in research by Tuyen Son Nguyen and Huan Buu Nguyen at Can Tho University, Vietnam, as well as by Prof. Dr. Mona H. Soliman and Dr. Mamdouh Farag. To assess teacher performance, the Evaluation of Teaching Performance Questionnaire (CEID) from the Centro de Estudios e Investigaciones Docentes, and the Staff Performance Questionnaire revised by the University of Fraser Valley in August 2011 were utilized (4,10,15,16). The data analysis was performed using SPSS version 25.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…School plays an important role to improve student's self reliance. It is important to analyse student's self-reliance because it can be a solution to increase cognitive ability (Yudho et al, 2022), prevent bullying in school (Nasti et al, 2023), develop habit of mind (Rikizaputra et al, 2021), and understand sustainibility program (Susanti et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This has implications for teacher recruitment policies, teacher training programs concerning student profiles, and identifying and applying appropriate methodologies for their performance in the classroom (Rao, 2016). The motivation of prospective physical education teachers is as important as the self-confidence they have when attending college lessons or at their preparatory stage in teaching their students in the classroom (Yudho et al, 2022). This is one of the variables that must be prioritized in every teaching mission for prospective teacher education at the tertiary level.…”
Section: Introductionmentioning
confidence: 99%